Understanding the antecedents of mobile social media acceptance during the public health crisis maintenance stage. (May 2022) - Wang, Houcai; Xiong, Li
Abstract: Mobile social media experienced explosive growth during the COVID-19 pandemic. To understand the underlying causes of users' acceptance towards mobile social media, this study draws upon the uses and gratifications theory, media dependency theory, and related literature of individuals' perceived appraisal (perceived trust, perceived benefits, and perceived risk) to explore the determinants that influenced mobile social media acceptance during the public health crisis maintenance stage. Data were obtained from 724 mobile social media users in China through an online paid questionnaire survey platform. The results revealed that perceived trust and perceived benefits positively affected information seeking and information sharing, which jointly influenced an individual's intention to use mobile social media during the public health crisis maintenance stage. Social media dependency also positively affected mobile social media users' usage intentions. However, perceived risk negatively influenced information seeking and information sharing. The results of this study offer valuable theoretical and practical implications for crisis communication researchers, emergency management practitioners, and mobile social media platforms.